STRATEGI MEMBINA HUBUNGAN ANTARA KONSELOR DAN KLIEN - Mirna Ari Mulyani (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
counselors have a duty to recognize and deal with the right elements that seem paradoxical relationship. Because effectiveness of therapy depends so much on the quality of the relationship between counselor and client, counselor basic attitude is very significant. Acceptance and understanding have considerable consequences on the psychological climate of the interview. This climate makes these attitudes have important implications for the evaluation of the client's own personality. A key to effective climate attitude is a counselor with the assumption that the internal reference frame, which is an attempt to understand the client to take a client's view of the situation. The counselor must have additional characteristics of warmth, intelligence, humility flexibility, and a willingness to share responsibility jawab.Salah the primary functions of this relationship is to provide support for clients, especially in a crisis. Support comfort and security through the development of optimal living conditions. Support is generally considered to be the goal of psychological counseling and often a necessary condition before a solution can be found more cognitive.